Comparison of the Efficacy of Moxifloxacin Preparations in the Therapy of Conjunctivitis - A. Yu. Malygin; A. B. Lisitsyn; O. M. Selina (Oftalʹmologiâ)
Purpose. To evaluate the efficacy and safety of therapy in patients with bacterial conjunctivitis using Moxioftan® eye drops, 5 mg/mL, 5 mL (JADRAN-GALENSKI LABORATORIJ, Croatia), and Vigamox® eye drops, 5 mg/mL, 5 mL (Alcon Laboratories, Inc., USA).Patients and methods. A multicenter, open-label, randomized, comparative clinical trial included 220 patients who were randomized into the Moxioftan® (moxifloxacin) group (n = 110) as the main group or the Vigamox® (moxifloxacin) group (n = 110) as the control group. The primary efficacy endpoint was the frequency of clinical cure, defined as the disappearance of clinical signs of bacterial conjunctivitis at the final study visit (visit 5, day 9 ± 1). Secondary efficacy endpoints included the degree of bacterial eradication, defined as the absence of growth of the primary pathogen identified in the baseline conjunctival smear by day 9 ± 1, dynamics of clinical symptoms of bacterial conjunctivitis, treatment efficacy assessed by both investigators and patients. The safety evaluation included an assessment of the incidence of adverse events, serious adverse events, and their potential relationship to the investigational and comparator drugs. Statistical analysis was performed using the R statistical package v. 3.2.1 and Statistica 10. Results. The clinical cure rate by day 9 ± 1 of the study (visit 5) was 100 % in both the main and control groups. The severity of clinical symptoms of bacterial conjunctivitis decreased equally in both groups by the final study visit: –5.32 ± 1.71 and –5.55 ± 1.40 points in the main and control groups, respectively (p > 0.05). By day 9 ± 1 of the study, the overall efficacy rating of “good” prevailed in both groups. According to patients, good efficacy was noted in 97.27 % and 94.55 % of cases in the main and control groups, respectively. According to investigators, good efficacy was observed in 96.36 % and 94.55 % of patients in the main and control groups, respectively. The safety analysis demonstrated a comparable safety profile for Moxioftan® and Vigamox®. The incidence and nature of adverse events were similar between the groups.Conclusion: The study demonstrated comparable efficacy and a similar safety profile of Moxioftan® eye drops compared to Vigamox® in the treatment of patients with bacterial conjunctivitis.